Tracing the Traces of Culture Acculturation and Islamic Values: Sacred Traditions of the Dukuh Dalam Traditional Village Community in Cikelet Garut - Lisyani, Nisa; Kosasih, Aceng; Sumarna, Elan (Universitas Islam Negeri Sumatera Utara, 2025)
This study aims to explore the Islamic values contained in the traditions of the people of Kampung Adat Dukuh Dalam in Cikelet District, Garut Regency. This study is important because the traditions of indigenous peoples are often considered mere cultural heritage, whereas in the context of Kampung Adat Dukuh Dalam, these traditions are a direct reflection of the Islamic value system integrated in social and spiritual life. Using a qualitative approach with a descriptive method, this research examines the history of Kampung Adat Dukuh Dalam, the variety of traditions that have developed, and the Islamic values contained in the traditions as a guide to life. The results show that the people of Kampung Adat Dukuh Dalam live within the framework of customs sourced from the teachings of Islam brought by Sheikh Abdul Jalil. Islamic values are reflected in the form of daily, monthly, and annual traditions that are full of aqidah, worship, and moral values. In the midst of the swift flow of modernization and external influences, the community is still able to maintain its cultural identity by filtering external influences based on the principles of Islamic teachings. They reject elements that contradict the Shari'ah, and adopt those that are in line through the preservation of traditions, faith-based non-formal education, and the strengthening of communities based on Islamic values.